Respuesta :
This is a linear function of the form y = mx + b,
m = 5/7 (given) → y = (5/7).x + b. This function passes through (8, -5), where
(x=8) & (y= -5)
To calculate b , replace x & y by their respective values:
-5 = (5/7).(8) + b; → -5 = 40/7 + b;→ b= -5 - 40/7 = -75/7,
Finally the equation is y= f(x) = (5/7).x -75/7
m = 5/7 (given) → y = (5/7).x + b. This function passes through (8, -5), where
(x=8) & (y= -5)
To calculate b , replace x & y by their respective values:
-5 = (5/7).(8) + b; → -5 = 40/7 + b;→ b= -5 - 40/7 = -75/7,
Finally the equation is y= f(x) = (5/7).x -75/7